2016
DOI: 10.1097/mao.0000000000001043
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation Improves Spatial Release From Masking and Restores Localization Abilities in Single-sided Deaf Patients

Abstract: The present data demonstrates that spatial release from masking can be restored in patients with SSD using a cochlear implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 42 publications
3
53
0
2
Order By: Relevance
“…Initial studies have shown improvement with localization (Arndt et al 2011; Firszt et al 2012; Hansen et al 2013; Zeitler et al 2015) and speech recognition in noise, depending on the type and location (Bernstein et al 2016; Grossman et al 2016; Zeitler et al 2015); however, considerable work remains to fully understand communication deficits and expected benefits from cochlear implantation. The range of performance for unaided/nonimplanted UHL participants in the current study (and others), provides a framework to gauge potential benefits gained from cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have shown improvement with localization (Arndt et al 2011; Firszt et al 2012; Hansen et al 2013; Zeitler et al 2015) and speech recognition in noise, depending on the type and location (Bernstein et al 2016; Grossman et al 2016; Zeitler et al 2015); however, considerable work remains to fully understand communication deficits and expected benefits from cochlear implantation. The range of performance for unaided/nonimplanted UHL participants in the current study (and others), provides a framework to gauge potential benefits gained from cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of binaural function has been associated with reduced localization, speech understanding in noise, and quality of life (QoL) in SSD patients [Cabral et al, 2016;Finke et al, 2017;Grossmann et al, 2016;Kuppler et al, 2013;Nawaz et al, 2014;Tokita et al, 2014;Wie et al, 2010]. For SSD patients, restoration of binaural function is possible with a cochlear implant (CI).…”
Section: Introductionmentioning
confidence: 99%
“…A study of CI for adult-acquired SSD was reviewed. Two systematic reviews [13,14] and several subsequent reports [15][16][17][18] yielded similar results. These are summarized as follows.…”
Section: Cochlear Implantmentioning
confidence: 56%